An insight into the histopathology of oral potentially malignant disorders and malignant neoplasms of head and neck - Iqbal, Fatima; Bashir, Nasiha (Journal of the Pakistan Medical Association, 2025)
This retrospective, descriptive, cross-sectional study was planned to analyse histopathological variations in oral potentially malignant disorders and malignant tumours of the head and neck region. Incisional and excisional biopsies referred to the histopathology laboratory of Peshawar Medical College, Pakistan, between 2020 and 2022 were reviewed by two pathologists to confirm the diagnosis. The World Health Organisation criterion of diagnosis and classification was adopted to review and validate the histopathological features. A total of 16 oral potentially malignant disorders and 77 head and cancer biopsies were included. Among the disorders, lichen planus was common, presenting as subepithelial lymphocytic infiltration in 11(100%) cases. Among the head and neck tumours, oral squamous cell carcinoma was the foremost cancer in which cells were arranged in a nest pattern 37(84%), followed by basal cell carcinoma showing nodular type 10 (83%). The histopathological variations of the lesions identified may assist pathologists in better diagnosis. Key Words: Histopathology, Head and neck cancer, Squamous cell carcinoma, Lichen planus.